COVID-19 and Distance Learning: Effects on Georgia State University School of Public Health Students - Armstrong-Mensah, Elizabeth; Ramsey-White, Kim; Yankey, Barbara; Self-Brown, Shannon (Frontiers in Public Health, 2020)
.